Testosterone for Managing Treatment-related Fatigue in Patients With Metastatic Renal Cell Carcinoma: A Phase 2 Randomized Study FARETES. (April 2021) - Tsimafeyeu, Ilya; Tishova, Yulia; Zukov, Ruslan; Borisov, Pavel; Bondarenko, Anastasia; Zakurdaeva, Kristina
Abstract : Background: Fatigue is one of the most common adverse events of systemic therapy in patients with metastatic renal cell carcinoma (RCC). The aim of multicenter randomized phase 2 study was to determine the efficacy and safety of testosterone in patients with fatigue developed during targeted therapy. Patients and Methods: Male patients with metastatic clear-cell RCC, normal prostate-specific antigen level, low testosterone level, and no evidence of hypothyroidism receiving first-line sunitinib or pazopanib with fatigue were randomly assigned (1:1) to either testosterone undecanoate (1000 mg) and targeted therapy or targeted therapy alone. The primary endpoint was the mean change of fatigue from baseline to 28 days according to the Functional Assessment of Chronic Illness Therapy—Fatigue scale. Secondary endpoints were safety, Functional Assessment of Cancer Therapy—Kidney Symptom Index 19, testosterone serum concentrations, red blood cell count, and hemoglobin level. Results: Sixty patients were assigned to receive testosterone and targeted therapy (N=30) or targeted therapy alone (N=30). As of the data cutoff on December 30, 2019, median follow-up was 18.2 months. The study achieved its primary endpoint based on the significant differences at day 28 favoring testosterone over targeted therapy alone regarding the decreased level of fatigue (difference between groups, 22.5 points; 95% confidence interval, 18.4-26.6; P =0.012). Significant changes in scores demonstrating the enhanced quality of life with testosterone compared with targeted therapy were also observed for Functional Assessment of Cancer Therapy—Kidney Symptom Index 19 disease-related symptoms ( P =0.01). There were nonsignificant differences in red blood cell count and hemoglobin level between the 2 groups (all P >0.05). Conclusion: Male patients with metastatic RCC and hypogonadism receiving testosterone had less fatigue and better symptom control during targeted therapy.